Core-shell grafted organic-inorganic covalent hybrid fluid loss additives and methods of making same

CN122978367APending Publication Date: 2026-10-27CNPC XIBU DRILLING ENG +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611484119.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明提供了一种核-壳接枝有机-无机共价杂化降滤失剂及其制备方法,克服了上述现有技术之不足,其能有效解决现有降滤失剂存在高温稳定性差,有机-无机界面采用物理共混导致性能失效的问题

Benefits of technology

第一,高温稳定性优异和界面结合与抗剪切性能突出。本发明高温稳定性优异和界面结合与抗剪切性能突出,得益于具有核-壳接枝的有机-无机共价杂化结构,本发明以硅烷改性纳米羟基磷灰石为无机内核,通过表面接枝共聚有机支链,形成以无机内核为中心、有机支链为壳层的核壳接枝的有机-无机共价杂化结构的降滤失剂,其界面间通过Si-O-P/Si-O-Ca共价键及Si-O-Si自缩聚网络实现分子级结合,使得产品界面结合强度较物理共混体系显著提升;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of drilling fluid additives, and is a core-shell grafted organic-inorganic covalent hybrid fluid loss additive and a preparation method thereof.The core-shell grafted organic-inorganic covalent hybrid fluid loss additive is first prepared by modifying nano-hydroxyapatite of a low-cost biological source through silane to obtain silane-modified nano-hydroxyapatite, and then obtained by grafting copolymerization of organic branches on the surface of the silane-modified nano-hydroxyapatite with the silane-modified nano-hydroxyapatite as an inorganic core.The additive has excellent high-temperature stability, outstanding interface bonding capacity and shear resistance, and has the characteristics of low tackiness, good rheological properties, high biodegradability, good salt and calcium resistance, and low cost.The additive effectively solves the problems of poor high-temperature stability, poor interface bonding force and performance failure of existing fluid loss additives due to physical blending of the organic-inorganic interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of drilling fluid additives, specifically a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer and its preparation method. Background Technology

[0002] As oil and gas exploration and development continue to advance into deeper and ultra-deep formations (well depth > 6000m), salt-gypsum layers, and marine high-calcium-magnesium reservoirs, bottom-hole static temperatures have generally exceeded 200℃, with some ultra-deep wells even reaching over 220℃. Formation water salinity can also reach saturated brine levels. During long-term circulation, drilling fluids continuously endure the combined effects of high temperature, high shear, and multi-ion contamination, placing extremely stringent comprehensive requirements on the thermal stability, salt resistance, performance durability, and environmental compatibility of filtration fluid reducers.

[0003] Despite technological advancements, existing filtration loss reducer products have made some progress in individual indicators such as temperature resistance and salt tolerance, but they still struggle to meet the comprehensive needs of ultra-deep well construction. Their core shortcomings are mainly: First, the performance of linear high-temperature polymers (HTHPs) deteriorates sharply after long-term thermal aging. Most current mainstream products are linear AM / AMPS binary and ternary copolymers (such as commercially available NPAM-8000 and AM / AMPS copolymers). Some heat-resistant products improve the rigidity of the main chain by introducing naphthalene rings and octavinyl POSS groups, but the molecular chain is still essentially a linear long-chain structure. During long-term thermal aging at 220℃, the CC main chain is prone to random breakage, resulting in a significant decrease in molecular weight. This directly leads to a sharp drop in drilling fluid viscosity and a surge in HTHP filtration loss, failing to meet the performance stability requirements for long-term circulation operations in ultra-deep wells. Simultaneously, severe entanglement between linear molecular chains significantly increases the plastic viscosity of the drilling fluid after addition, increasing circulation resistance and reducing mechanical drilling speed, making it difficult to achieve the goal of "low viscosity, high efficiency, and reduced filtration loss." Secondly, the interfacial bonding in physically blended organic-inorganic composite systems is prone to failure. Existing organic-inorganic composite filtration reducers often employ simple physical mixing of nano-SiO2, montmorillonite, inorganic fillers, and polymer solutions. The inorganic phase and organic molecular chains are only bonded by van der Waals forces, lacking chemical bonds. Under the high-shear and high-temperature environments (above 200°C) of drilling, the two-phase interface is highly susceptible to debonding, leading to agglomeration and sedimentation of inorganic nanoparticles, completely losing their ability to seal mud cake pores. The large agglomerated particles also easily clog downhole tools, increasing the load on solids control equipment and the cost of solids processing. While increasing the system viscosity through macromolecular crosslinking can only delay particle sedimentation to a certain extent, it does not solve the fundamental problem of covalent bonding between the two phases, and performance degradation remains significant under long-term high-temperature and high-shear conditions. Third, high-temperature resistance and biodegradability are incompatible. Natural polymer-modified filtration reducers (starch, cellulose, lignin-based, etc.) have excellent biodegradability, but their weak bonds such as glycosidic bonds within the molecule have poor thermal stability, and their upper temperature resistance is generally ≤180℃, making them completely unsuitable for deep and ultra-deep well conditions. On the other hand, fully synthetic polymer filtration reducers with a temperature resistance of over 200℃ mostly have a rigid structure with a full carbon chain backbone, making them difficult to biodegrade and meet environmental protection requirements, thus facing the problem of "high temperature resistance but not environmental protection, and environmental protection but not high temperature resistance." Fourth, there are relatively few nonlinear structure filtration loss reducers. Currently available products and the vast majority of published patents primarily use linear molecular structures. Although research has reported the application of hyperbranched polymers in drilling fluids, such as the Chinese patent document CN116063623B which discloses a method for preparing a hyperbranched polymer for drilling fluids and a drilling fluid thereof, this hyperbranched polymer for drilling fluids comprises: copolymerizing organic acid monomers, organic amide monomers, a first branching agent, a second branching agent, and a chain transfer agent under the action of a pH adjuster and a chain transfer agent to obtain the hyperbranched polymer for drilling fluids. The reversible addition-fragmentation chain transfer (RAFT) polymerization method provided by this invention employs a rapid polymerization process, using diene monomers, branching agents, and chain transfer agents to prepare a water-soluble snowflake-like hyperbranched polymer filtration loss reducer with high polymerization rate and high conversion in an aqueous solution system. This double-layered branched structure exhibits good solubility, high rheological properties, non-crosslinking, and a large number of branched end groups. The resulting product has a narrow molecular weight distribution, good temperature resistance, and low viscosity effect. However, existing hyperbranched filtration loss reducers are mainly composed of pure organic hyperbranched structures without the introduction of an inorganic rigid core, and the preparation process is complex, requiring the use of controllable living polymerization methods such as RAFT. Fifth, high-end temperature-resistant solutions are costly. Existing technologies for improving the temperature resistance of filtration loss reducers mostly rely on expensive raw materials such as octavinyl POSS, special heterocyclic monomers, and polycyclic monomers, resulting in high synthesis costs and hindering large-scale application. On the other hand, low-cost, bio-based, and highly rigid inorganic fillers are only used as physical filler additives and do not form covalent bonds with polymers through surface modification. Therefore, they cannot fully exert their role in rigid support and improving thermal stability, resulting in very limited performance improvements.

[0004] Therefore, there is an urgent need to develop a filtration loss reducer that can simultaneously meet the comprehensive requirements of high-temperature stability, shear resistance, low viscosity-increasing performance, biodegradability, and cost control under the harsh working conditions of ultra-deep wells. Summary of the Invention

[0005] This invention provides a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer and its preparation method, which overcomes the shortcomings of the prior art. It can effectively solve the problems of poor high-temperature stability and performance failure caused by physical blending of organic-inorganic interfaces in existing filtration loss reducers.

[0006] One of the technical solutions of the present invention is achieved through the following measures: a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer, the components of which, by weight, include 3 to 5 parts of silane-modified nano-hydroxyapatite, 38 to 42 parts of acrylamide (AM), 18 to 22 parts of 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 5 to 7 parts of N-vinylpyrrolidone (NVP), 2 to 3 parts of dodecyl methacrylate (LMA), 0.08 to 0.15 parts of N,N'-methylenebisacrylamide (MBA), 3 to 5 parts of sodium acrylamide lignin sulfonate, 0.3 to 0.4 parts of composite initiator, and 130 to 140 parts of deionized water.

[0007] The following are further optimizations and / or improvements to one of the above-mentioned technical solutions: The above-mentioned silane-modified nano-hydroxyapatite is obtained by modifying nano-hydroxyapatite with silane coupling agent KH-570.

[0008] The above-mentioned acrylamide-based sodium lignin sulfonate is obtained by two-step modification of sodium lignin sulfonate, formaldehyde, dimethylamine and acryloyl chloride.

[0009] The above-mentioned composite initiator is composed of ammonium persulfate and sodium bisulfite in a mass ratio of (0.8 to 1.2): (0.8 to 1.2).

[0010] The above-mentioned core-shell grafted organic-inorganic covalent hybrid filtration loss reducer is obtained by the following steps: S1, Preparation of silane-modified nano-hydroxyapatite: Nano-hydroxyapatite was ultrasonically dispersed in water, and then silane coupling agent KH-570 was added to obtain a mixture. After adjusting the pH value of the mixture, the mixture was heated and stirred to react. After centrifugation, washing and drying, silane-modified nano-hydroxyapatite was obtained. S2, Preparation of acrylamide-based sodium lignin sulfonate: Sodium lignin sulfonate was dissolved in sodium hydroxide solution, and the pH was adjusted to 10 to 11. Formaldehyde and dimethylamine were then added and mixed to carry out the Mannich reaction. The system was then cooled, and acryloyl chloride was added to carry out the amidation reaction. After the reaction was completed, the pH was adjusted to 5 to 6, and a precipitate was formed. After washing and drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, Low-temperature in-situ copolymerization: Silane-modified nano-hydroxyapatite is added to deionized water and ultrasonically dispersed. Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, dodecyl methacrylate, N,N'-methylenebisacrylamide and sodium acrylamide lignin sulfonate are added sequentially and stirred until homogeneous to obtain a mixture. The pH value of the mixture is adjusted, and a composite initiator is added to the mixture under a nitrogen atmosphere. After stirring and polymerization reaction, a viscous colloidal polymer is obtained. S4, Post-processing: The viscous colloidal polymer is granulated, dried, crushed and sieved to obtain a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer.

[0011] In step S1 above, the mass ratio of nano-hydroxyapatite to silane coupling agent KH-570 is 1:(0.1 to 0.2), and the amount of water added is 9 to 10 times the mass of nano-hydroxyapatite.

[0012] In step S1 above, the pH value of the mixture is adjusted by using dilute ammonia water with a mass concentration of 8% to 12% to adjust the pH value of the mixture to 8.5 to 9.0, raising the temperature to 55°C to 65°C, and stirring the reaction for 3.5 to 4.5 hours.

[0013] In step S1 above, centrifugation is performed at 7500 rpm to 8500 rpm for 15 to 20 minutes, washing is performed with deionized water 3 to 4 times, and drying is performed under vacuum at 55°C to 65°C for 7.5 to 8.5 hours.

[0014] In step S2 above, the molar ratio of sodium lignosulfonate:formaldehyde:dimethylamine is 1:(1.0 to 1.5):(1.0 to 1.5), the mass ratio of acryloyl chloride to sodium lignosulfonate is 1:(0.4 to 0.8), the mass concentration of sodium hydroxide solution is 8% to 12%, and the amount of sodium hydroxide solution added is 5 to 15 times the mass of sodium lignosulfonate.

[0015] In step S2 above, the Mannich reaction is carried out at 60°C to 70°C for 2 to 3 hours, and the amidation reaction is carried out at 0°C to 5°C for 1 to 2 hours.

[0016] In step S3 above, during stirring and mixing, the stirring temperature is 25℃ to 30℃, the stirring speed is 300r / min to 350r / min, and the pH value of the mixture is adjusted to 7.0 to 7.5 using a 10% sodium hydroxide solution.

[0017] In step S3 above, the stirring and polymerization reaction specifically occur at a stirring rate of 150 r / min to 200 r / min and a temperature of 42°C to 45°C for 3.5 h to 4.0 h.

[0018] In step S4 above, granulation involves feeding the viscous colloidal polymer into an extrusion granulator to produce uniform particles with a particle size of 2 mm to 5 mm, and drying involves drying the particles at 70°C to 75°C for 7.5 h to 8.5 h.

[0019] In step S4 above, the sieving is performed using an 80-mesh standard sieve.

[0020] The second technical solution of the present invention is achieved through the following measures: a method for preparing a core-shell grafted organic-inorganic covalent hybrid filtration loss reducing agent, comprising the following steps: S1, Preparation of silane-modified nano-hydroxyapatite: Nano-hydroxyapatite was ultrasonically dispersed in water, and then silane coupling agent KH-570 was added to obtain a mixture. After adjusting the pH value of the mixture, the mixture was heated and stirred to react. After centrifugation, washing and drying, silane-modified nano-hydroxyapatite was obtained. S2, Preparation of acrylamide-based sodium lignin sulfonate: Sodium lignin sulfonate was dissolved in sodium hydroxide solution, and the pH was adjusted to 10 to 11. Formaldehyde and dimethylamine were then added and mixed to carry out the Mannich reaction. The system was then cooled, and acryloyl chloride was added to carry out the amidation reaction. After the reaction was completed, the pH was adjusted to 5 to 6, and a precipitate was formed. After washing and drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, Low-temperature in-situ copolymerization: Silane-modified nano-hydroxyapatite is added to deionized water and ultrasonically dispersed. Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, dodecyl methacrylate, N,N'-methylenebisacrylamide and sodium acrylamide lignin sulfonate are added sequentially and stirred until homogeneous to obtain a mixture. The pH value of the mixture is adjusted, and a composite initiator is added to the mixture under a nitrogen atmosphere. After stirring and polymerization reaction, a viscous colloidal polymer is obtained. S4, Post-processing: The viscous colloidal polymer is granulated, dried, crushed and sieved to obtain a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer.

[0021] This invention relates to a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer. Firstly, it is obtained by modifying low-cost, bio-based nano-hydroxyapatite with silane. Then, using the silane-modified nano-hydroxyapatite as the inorganic core, organic branches are grafted onto its surface to copolymerize. It not only exhibits excellent high-temperature stability, outstanding interfacial bonding ability, and superior shear resistance, but also demonstrates significant low viscosity and good rheological properties. Furthermore, it possesses high biodegradability, good salt and calcium resistance, and low cost. This effectively solves the problems of poor high-temperature stability and poor interfacial bonding and performance failure caused by physical blending of the organic-inorganic interface in existing filtration loss reducers. Detailed Implementation

[0022] This invention is not limited to the following embodiments, and specific implementation methods can be determined according to the technical solutions and actual conditions of this invention. Unless otherwise specified, all chemical reagents and chemicals mentioned in this invention are well-known and commonly used chemical reagents and chemicals in the prior art; unless otherwise specified, all percentages in this invention are mass percentages; unless otherwise specified, all solutions in this invention are aqueous solutions with water as the solvent, for example, hydrochloric acid solution is an aqueous solution of hydrochloric acid; room temperature in this invention generally refers to a temperature between 15°C and 25°C, generally defined as 25°C.

[0023] The present invention will be further described below with reference to embodiments: Example 1: The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer comprises, by weight, 3 to 5 parts silane-modified nano-hydroxyapatite, 38 to 42 parts acrylamide (AM), 18 to 22 parts 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 5 to 7 parts N-vinylpyrrolidone (NVP), 2 to 3 parts dodecyl methacrylate (LMA), 0.08 to 0.15 parts N,N'-methylenebisacrylamide (MBA), 3 to 5 parts sodium acrylamide lignin sulfonate, 0.3 to 0.4 parts composite initiator, and 130 to 140 parts deionized water.

[0024] In this invention, acrylamide (AM) is a water-soluble olefinic basic monomer. Its role is to form the main chain skeleton of the organic branch chain, provide sufficient amide group adsorption sites, ensure good water solubility and water dispersibility of the product, and provide a chain growth skeleton for the covalent grafting of functional monomers and inorganic cores. 2-Acrylamido-2-methylpropanesulfonic acid (AMPS) is a strong anionic salt-resistant monomer. Its function is through the hydration of the strongly hydrated sulfonate group (-SO3). - A stable hydration layer is formed on the outside of the side chain, which inhibits the salting out and coiling of the molecular chain under high salt conditions; at the same time, the large-volume side groups generate a steric hindrance effect, which improves the thermal stability of the main chain, so that the product can still maintain more than 85% of its performance in a saturated brine system. N-Vinylpyrrolidone (NVP) is a heat-resistant rigid heterocyclic monomer. Its function is to embed the five-membered lactam heterocycle into the polymer backbone, improve the rigidity and steric hindrance of the chain segments, reduce the rotational freedom of the backbone bonds, and work synergistically with the inorganic rigid core (silane-modified nano-hydroxyapatite) to ensure the integrity of the polymer's molecular structure at high temperatures. Dodecyl methacrylate (LMA) is a long-chain alkyl hydrophobic functional monomer. Its function is to introduce hydrophobic dodecyl groups at the side positions of the branches, which are oriented to form a hydrophobic barrier on the filter cake surface, reducing the filter cake adhesion effect. At the same time, it helps to stabilize the cake structure through hydrophobic association, inhibits shale hydration dispersion, and endows the product with anti-collapse function. N,N'-methylenebisacrylamide (MBA) is a bifunctional, weakly crosslinked monomer. Its function is to create sparse covalent crosslinking points between adjacent branches by controlling the amount added (only 1 / 10 to 1 / 20 of that in conventional crosslinking systems), constructing a slightly spatial network structure. This results in a small increase in filtration loss after 32 hours of long-term thermal aging, while also avoiding viscosity increases caused by excessive crosslinking. Deionized water has a conductivity ≤10μS / cm. Its function is to serve as a polymerization reaction medium, ensuring uniform dispersion of monomers and inorganic particles, avoiding side reactions and uneven cross-linking caused by impurity ions, and ensuring a stable polymerization process.

[0025] Example 2: As an optimization of the above examples, silane-modified nano-hydroxyapatite is prepared by using nanoparticles with a particle size of 20nm to 50nm and a specific surface area of ​​80m². 2 / g to 120m 2 / g room temperature nano-hydroxyapatite (HAP) was obtained by modification with silane coupling agent KH-570.

[0026] The reaction mechanism of silane-modified nano-hydroxyapatite: The methoxysilane groups in the silane coupling agent KH-570, after hydrolysis, form silanol groups (Si-OH), which undergo dehydration condensation reactions with the phosphorohydroxyl groups (P-OH) and calcium hydroxyl groups (Ca-OH) on the surface of nano-hydroxyapatite, forming Si-OP and Si-O-Ca covalent bonds. Simultaneously, self-condensation reactions occur between the silanol groups (Si-OH) to form a Si-O-Si oligomer network, further coating the surface of the nano-hydroxyapatite. The density of polymerizable double bonds (methacryloyloxy) grafted onto the surface of the silane-modified nano-hydroxyapatite is 0.8 bonds / nm. 2 Up to 1.5 units / nm 2 .

[0027] In this invention, silane-modified nano-hydroxyapatite is used as the inorganic core of the core-shell grafted structure. Covalent bonds are formed through the copolymerization reaction of surface polymerizable double bonds (methacryloyloxy) with organic side chains, resulting in better interfacial bonding strength compared to physical blending. Simultaneously, the silane-modified nano-hydroxyapatite as the inorganic core also improves the product's thermal stability. Specifically: First, the high heat capacity and low coefficient of thermal expansion of the inorganic core can disperse local thermal stress, reducing chain breakage caused by thermal stress concentration; second, the Si-OP / Si-O-Ca covalent bonds at the core-shell interface have high bond energies (approximately 460 kJ / mol for Si-O and 360 kJ / mol for PO), making them less prone to breakage at high temperatures and maintaining structural integrity; third, the presence of the inorganic core reduces the volume fraction of the organic phase, decreasing the number of thermal degradation sites per unit volume.

[0028] Example 3: As an optimization of the above examples, acrylamide-based sodium lignosulfonate was obtained by two-step modification of sodium lignosulfonate, formaldehyde, dimethylamine and acryloyl chloride.

[0029] In this invention, sodium acrylamide-based lignin sulfonate is a biodegradable functional monomer. Its role is to introduce natural lignin aromatic structural units to help improve the temperature resistance of the polymer. At the same time, it provides biodegradable sites, so that the product has a biodegradability rate of ≥60% after 28 days, thus solving the problem of the difficulty in degradation of fully synthetic polymers.

[0030] Example 4: As an optimization of the above example, the composite initiator is composed of ammonium persulfate and sodium bisulfite in a mass ratio of (0.8 to 1.2): (0.8 to 1.2).

[0031] In this invention, a low-temperature redox initiation system is constructed using a composite initiator, which can efficiently initiate polymerization reactions at low temperatures (42°C to 45°C). The activation energy for low-temperature initiation is approximately 50 kJ / mol to 60 kJ / mol, which is about 55% lower than that for thermal initiation (thermal decomposition of potassium persulfate, activation energy of approximately 130 kJ / mol to 140 kJ / mol). Therefore, the polymerization reaction is stable and controllable, and the molecular weight of the branched chains and the crosslinking density can be precisely controlled, ensuring the stability of product batches.

[0032] Example 5: As an optimization of the above examples, a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer was obtained by the following steps: S1, Preparation of silane-modified nano-hydroxyapatite: Nano-hydroxyapatite (HAP) was ultrasonically dispersed in water, and then silane coupling agent KH-570 was added to obtain a mixture. After adjusting the pH value of the mixture, the mixture was heated and stirred to react. After centrifugation, washing and drying, silane-modified nano-hydroxyapatite was obtained. S2, Preparation of acrylamide-based sodium lignin sulfonate: Sodium lignin sulfonate was dissolved in sodium hydroxide solution, and the pH was adjusted to 10 to 11. Formaldehyde and dimethylamine were then added and mixed to carry out the Mannich reaction. The system was then cooled, and acryloyl chloride was added to carry out the amidation reaction. After the reaction was completed, the pH was adjusted to 5 to 6, and a precipitate was formed. After washing and drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, Low-temperature in-situ copolymerization: Silane-modified nano-hydroxyapatite is added to deionized water and ultrasonically dispersed. Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, dodecyl methacrylate, N,N'-methylenebisacrylamide and sodium acrylamide lignin sulfonate are added sequentially and stirred until homogeneous to obtain a mixture. The pH value of the mixture is adjusted, and a composite initiator is added to the mixture under a nitrogen atmosphere. After stirring and polymerization reaction, a viscous colloidal polymer is obtained. S4, Post-processing: The viscous colloidal polymer is granulated, dried, crushed and sieved to obtain a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer.

[0033] Example 6: As an optimization of the above example, in step S1, the mass ratio of nano-hydroxyapatite to silane coupling agent KH-570 is 1:(0.1 to 0.2), and the amount of water added is 9 to 10 times the mass of nano-hydroxyapatite.

[0034] Example 7: As an optimization of the above example, in step S1, the pH value of the mixture is adjusted by using dilute ammonia water with a mass concentration of 8% to 12% to adjust the pH value of the mixture to 8.5 to 9.0, raising the temperature to 55°C to 65°C, and stirring the reaction for 3.5h to 4.5h.

[0035] Example 8: As an optimization of the above example, in step S1, centrifugation is performed at 7500 rpm to 8500 rpm for 15 min to 20 min, washing is performed with deionized water 3 to 4 times, and drying is performed under vacuum at 55°C to 65°C for 7.5 h to 8.5 h.

[0036] Example 9: As an optimization of the above example, in step S2, the molar ratio of sodium lignosulfonate:formaldehyde:dimethylamine is 1:(1.0 to 1.5):(1.0 to 1.5), the mass ratio of acryloyl chloride to sodium lignosulfonate is 1:(0.4 to 0.8), the mass concentration of sodium hydroxide solution is 8% to 12%, and the amount of sodium hydroxide solution added is 5 to 15 times the mass of sodium lignosulfonate.

[0037] Example 10: As an optimization of the above example, in step S2, the Mannich reaction is carried out at 60°C to 70°C for 2 to 3 hours, and the amidation reaction is carried out at 0°C to 5°C for 1 to 2 hours.

[0038] Example 11: As an optimization of the above example, in step S3, during stirring and mixing, the stirring temperature is 25°C to 30°C, the stirring speed is 300 r / min to 350 r / min, and the pH value of the mixture is adjusted to 7.0 to 7.5 using a 10% sodium hydroxide solution.

[0039] Example 12: As an optimization of the above example, in step S3, the stirring and polymerization reaction specifically occurs at a stirring rate of 150 r / min to 200 r / min and a temperature of 42°C to 45°C for 3.5 h to 4.0 h.

[0040] Example 13: As an optimization of the above example, in step S4, granulation involves feeding the viscous colloidal polymer into an extrusion granulator to produce uniform particles with a particle size of 2 mm to 5 mm, and drying involves drying the particles at 70°C to 75°C for 7.5 h to 8.5 h.

[0041] Example 14: As an optimization of the above example, in step S4, the sieving is performed through an 80-mesh standard sieve.

[0042] Compared with the prior art, the beneficial effects of the present invention are as follows: First, it exhibits excellent high-temperature stability and outstanding interfacial bonding and shear resistance. The excellent high-temperature stability and outstanding interfacial bonding and shear resistance of this invention are attributed to its core-shell grafted organic-inorganic covalent hybrid structure. This invention uses silane-modified nano-hydroxyapatite as the inorganic core, and through surface grafting and copolymerization of organic branches, forms a core-shell grafted organic-inorganic covalent hybrid structure for reducing filtration loss. The interfaces achieve molecular-level bonding through Si-OP / Si-O-Ca covalent bonds and a Si-O-Si self-condensation network, resulting in a significantly improved interfacial bonding strength compared to physically blended systems. The advantages of this core-shell grafted organic-inorganic covalent hybrid structure are twofold: First, it exhibits excellent high-temperature stability. Using silane-modified nano-hydroxyapatite as the inorganic core effectively disperses thermal stress and blocks oxygen free radical attacks. Further polymerization with organic monomers results in excellent high-temperature stability. After hot rolling at 220℃ for 16 hours, its molecular structure remains intact, and the high-temperature, high-pressure HTHP filtration loss can be controlled between 9.8 mL and 10.9 mL. After long-term aging at 220℃ for 32 hours of continuous hot rolling, the increase in HTHP filtration loss is minimal, effectively controlling drilling fluid filtration loss in permeable formations. It is stably applicable to long-term drilling conditions in ultra-deep wells below 220℃, solving the problem of high-temperature chain breakage failure in existing linear polymers. Second, it demonstrates outstanding interfacial bonding and shear resistance. Because the inorganic and organic phases are firmly bonded by covalent bonds, the product of this invention does not separate or debond under high temperature and high shear, and the nanoparticles do not agglomerate or settle. After 1 hour of high shear at 12000 r / min, the product retains a high shear resistance, effectively solving the problems of interfacial debonding and particle agglomeration and settling in existing physical blending systems under high temperature and high shear. Secondly, it exhibits significant low viscosity-increasing properties and excellent rheological performance. This invention reduces molecular entanglement through core-shell grafting, achieving compatibility between temperature resistance and low viscosity. The grafted organic branches extend outward from the rigid inorganic core surface, forming a steric hindrance layer, effectively reducing inter-molecular chain entanglement. When the product dosage is 1.5%, the apparent viscosity of the drilling fluid is only 18 mPa·s to 22 mPa·s, which is at a low level among similar temperature-resistant filtration reduction agents. The viscosity change rate before and after thermal aging is lower than that of similar temperature-resistant filtration reduction agents, solving the technical problem of "high temperature resistance inevitably leads to viscosity increase." Third, it exhibits excellent biodegradability. The combination of bio-derived hydroxyapatite and biodegradable sodium lignosulfonate allows the product to withstand long-term temperatures up to 220℃ while maintaining a 28-day biodegradation rate of ≥60%, exhibiting virtually no fluorescence and not interfering with well logging operations. This overcomes the limitation of natural polymers having a temperature resistance limit of ≤180℃ and solves the problem of the difficulty in degrading fully synthetic polymers, making it suitable for drilling needs in ecologically sensitive areas. Fourth, it exhibits outstanding salt and calcium resistance. Through the strong hydration sulfonic acid groups provided by 2-acrylamido-2-methylpropanesulfonic acid (AMPS), this functional group is fully exposed to the aqueous phase, making the hydration layer more stable. In high-salt environments, the molecular chains are less prone to salting out and coiling. After hot rolling at 220℃ for 16 hours in a saturated brine (NaCl=26%) and 10% CaCl2 system, the API filtration loss can be controlled between 4.8 mL and 5.2 mL, and the HTHP filtration loss can be controlled between 11.3 mL and 11.8 mL. The system shows no flocculation, no stratification, and no precipitation. Its salt and calcium resistance is significantly superior to conventional linear copolymers, making it suitable for complex formations with high mineralization. Fifth, low cost and high performance. By replacing expensive POSS and special heterocyclic monomers with low-cost bio-derived hydroxyapatite, this invention achieves low raw material costs, low reaction energy consumption, and good batch stability through low-cost production of high-performance products, making it suitable for large-scale industrial production.

[0043] Example 15: This core-shell grafted organic-inorganic covalent hybrid filtration loss reducer comprises, by weight, 4 parts silane-modified nano-hydroxyapatite, 40 parts acrylamide (AM), 20 parts 2-acrylamido-2-methylpropanesulfonic acid (AMPS), 6 parts N-vinylpyrrolidone (NVP), 2.5 parts dodecyl methacrylate (LMA), 0.12 parts N,N'-methylenebisacrylamide (MBA), 4 parts sodium acrylamide lignin sulfonate, 0.35 parts composite initiator (ammonium persulfate and sodium bisulfite in a 1:1 mass ratio), and 135 parts deionized water, obtained according to the following steps: S1, Preparation of silane-modified nano-hydroxyapatite: 40g of nano-hydroxyapatite (particle size 30nm, specific surface area 100m²) was prepared. 2 / g) was ultrasonically dispersed in 360mL of water and ultrasonically dispersed at 300W, 40kHz for 30min. Then, 6g of silane coupling agent KH-570 was added to obtain a mixture. The pH of the mixture was adjusted to 8.5 with 10% dilute ammonia water. The mixture was then heated to 60℃ and stirred at a constant temperature for 4h. This allowed the silane to hydrolyze and dehydrate with the hydroxyl groups on the surface of hydroxyapatite to form Si-OP and Si-O-Ca covalent bonds. Simultaneously, Si-O-Si self-condensation formed a surface coating layer. After the reaction was completed, the mixture was centrifuged at 8000rpm for 15min, washed three times with deionized water, and vacuum dried at 60℃ for 8h to obtain silane-modified nano-hydroxyapatite. TGA analysis showed that the silane grafting amount was 3.2wt%, and the density of polymerizable double bonds on the surface graft was approximately 1.0 bonds / nm. 2 Characterized by FTIR, at 1635 cm⁻¹ -1 A C=C stretching vibration peak appears at 1720 cm⁻¹. -1 The presence of a C=O stretching vibration peak at this point proves that the KH-570 graft was successful. S2, Preparation of acrylamide-based sodium lignin sulfonate: The molar ratio of sodium lignin sulfonate:formaldehyde:dimethylamine was fixed at 1:1.2:1.2. 3g of sodium lignin sulfonate was dissolved in 30mL of 10% sodium hydroxide solution (pH 10.5). Then, 0.6g of formaldehyde and 0.9g of dimethylamine were added, and the Mannich reaction was carried out at 65℃ for 2.5h, so that the aminomethyl group was grafted onto the aromatic ring of lignin through the Mannich reaction. Subsequently, the system was cooled by 5℃, and 1.8g of acryloyl chloride was slowly added dropwise and kept at the temperature for 1.5h to carry out an amidation reaction, so that the amino group and acryloyl chloride underwent an amidation reaction to introduce polymerizable double bonds. After the reaction was completed, the pH was adjusted to 5.5 with dilute hydrochloric acid, and a precipitate was precipitated. After washing with ethanol and vacuum drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, low-temperature in-situ copolymerization: 4g of silane-modified nano-hydroxyapatite was added to 135g of deionized water and ultrasonically dispersed for 25min. Then, 40g of acrylamide, 20g of 2-acrylamido-2-methylpropanesulfonic acid, 6g of N-vinylpyrrolidone, 2.5g of dodecyl methacrylate, and 0.12g of [unspecified ingredient] were added sequentially. N,N'-methylenebisacrylamide and 4g of sodium acrylamide lignin sulfonate were dissolved and mixed until homogeneous under stirring at 30℃ and 350r / min to obtain a mixture. The pH of the mixture was adjusted to 7.2 with a 10% sodium hydroxide solution. The mixture was then transferred to a polymerization reactor and sealed. Nitrogen gas with a purity ≥99.9% was introduced at a flow rate of 0.8L / min for 30 minutes to completely remove oxygen. The polymerization reactor was heated to 43℃ and held at that temperature for 10 minutes. 0.35g of composite initiator (dissolved in a small amount of deionized water) was added dropwise to the polymerization reactor within 20 minutes. The stirring rate was maintained at 200r / min, and polymerization was carried out at that temperature for 4 hours to obtain a viscous colloidal polymer. S4, Post-processing: The viscous colloidal polymer is fed into an extruder and granulated to produce uniform particles with a particle size of 2 mm to 5 mm. Then, the particles are spread evenly in a hot air drying oven and dried at 72°C for 8 hours, controlling the moisture content of the particles to ≤5%. Finally, the dried particles are fed into a high-speed pulverizer for crushing and passing through an 80-mesh standard sieve. The resulting core-shell grafted organic-inorganic covalent hybrid filtration loss reducer is labeled as A1.

[0044] Example 16: The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer differs from that in Example 15 in that: The components, by weight, include 3 parts silane-modified nano-hydroxyapatite, 38 parts acrylamide, 22 parts 2-acrylamido-2-methylpropanesulfonic acid, 5 parts N-vinylpyrrolidone, 3 parts dodecyl methacrylate, 0.15 parts N,N'-methylenebisacrylamide, 5 parts sodium acrylamide lignin sulfonate, 0.4 parts composite initiator (ammonium persulfate and sodium bisulfite in a 1:1 mass ratio), and 140 parts deionized water. In step S3, low-temperature in-situ copolymerization, "adjust the pH of the mixture to 7.2 with a 10% sodium hydroxide solution by mass" is replaced with "adjust the pH of the mixture to 7.5 with a 10% sodium hydroxide solution by mass"; "heat the polymerization reactor to 43°C and hold for 10 min" is replaced with "heat the polymerization reactor to 45°C and hold for 10 min". In step S4 post-processing, "drying with hot air at 72°C for 8 hours" is replaced with "drying with hot air at 75°C for 8 hours"; the remaining steps are the same as in Example 15, and the obtained core-shell grafted organic-inorganic covalent hybrid filtration loss reducer is labeled as A2.

[0045] Example 17: The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer differs from that in Example 15 in that: The components, by weight, include 5 parts silane-modified nano-hydroxyapatite, 42 parts acrylamide, 18 parts 2-acrylamido-2-methylpropanesulfonic acid, 7 parts N-vinylpyrrolidone, 2 parts dodecyl methacrylate, 0.1 parts N,N'-methylenebisacrylamide, 3 parts sodium acrylamide lignin sulfonate, 0.3 parts composite initiator (ammonium persulfate and sodium bisulfite in a 1:1 mass ratio), and 130 parts deionized water. In step S3, low-temperature in-situ copolymerization, "adjust the pH of the mixture to 7.2 with a 10% sodium hydroxide solution by mass" is replaced with "adjust the pH of the mixture to 7.0 with a 10% sodium hydroxide solution by mass"; "heat the polymerization reactor to 43°C and hold for 10 min" is replaced with "heat the polymerization reactor to 42°C and hold for 10 min". In step S4 post-processing, "drying with hot air at 72°C for 8 hours" is replaced with "drying with hot air at 70°C for 8 hours"; the remaining steps are the same as in Example 15, and the resulting core-shell grafted organic-inorganic covalent hybrid filtration loss reducer is labeled A3.

[0046] Example 18: The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer differs from that in Example 15 in that: The components, by weight, include 4 parts silane-modified nano-hydroxyapatite, 40 parts acrylamide, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 6 parts N-vinylpyrrolidone, 2.5 parts dodecyl methacrylate, 0.12 parts N,N'-methylenebisacrylamide, 4 parts sodium acrylamide lignin sulfonate, 0.35 parts composite initiator, and 135 parts deionized water; In step S1, the preparation of silane-modified nano-hydroxyapatite, the step of "adding 6g of silane coupling agent KH-570" was replaced with "adding 4.8g of silane coupling agent KH-570," that is, the amount of silane coupling agent KH-570 added was adjusted from 15% to 12%, so that the density of polymerizable double bonds grafted onto the surface of the silane-modified nano-hydroxyapatite was approximately 0.8 bonds / nm. 2 The remaining steps are the same as in Example 15, and the resulting core-shell grafted organic-inorganic covalent hybrid filtration reducer is labeled A4.

[0047] Example 19: The core-shell grafted organic-inorganic covalent hybrid filtration reducer differs from that in Example 15 in that (the amount of N,N'-methylenebisacrylamide is different): The components, by weight, include 4 parts silane-modified nano-hydroxyapatite, 40 parts acrylamide, 20 parts 2-acrylamido-2-methylpropanesulfonic acid, 6 parts N-vinylpyrrolidone, 2.5 parts dodecyl methacrylate, 0.08 parts N,N'-methylenebisacrylamide, 4 parts sodium acrylamide lignin sulfonate, 0.35 parts composite initiator (ammonium persulfate and sodium bisulfite in a 1:1 mass ratio), and 135 parts deionized water; the remaining steps are the same as in Example 15. The resulting core-shell grafted organic-inorganic covalent hybrid filtration loss reducer is labeled A5.

[0048] Comparative Example 1: The filtration loss reducing agent is a commercially available polyacrylamide-based filtration loss reducing agent (NPAM-8000, a linear structure with a molecular weight of approximately 8 million).

[0049] Comparative Example 2: The filtration loss reducing agent is a commercially available sulfonated phenolic resin filtration loss reducing agent (sulfonated phenolic resin filtration loss reducing agent SMP-1).

[0050] Comparative Example 3: The filtration loss reducer is a commercially available AM / AMPS binary copolymer filtration loss reducer (provided by Sichuan Hongsheng Petroleum Engineering Technology Service Co., Ltd., which has a linear structure and a molecular weight of approximately 2 million).

[0051] Comparative Example 4: The filtration loss reducer is a commercially available low-viscosity polyanionic cellulose PAC-LV (provided by Nanjing Liangyou Chemical Co., Ltd.).

[0052] Comparative Example 5: The difference between this filtration loss reducer and Example 15 is that in the components, "4 parts silane-modified nano-hydroxyapatite" is replaced with "4 parts nano-hydroxyapatite", that is, silane-modified nano-hydroxyapatite is replaced with an equal amount of unmodified nano-hydroxyapatite. Step S3, physical blending: Nano-hydroxyapatite was added to 135g of deionized water and ultrasonically dispersed for 25min. Then, 40g of acrylamide, 20g of 2-acrylamido-2-methylpropanesulfonic acid, 6g of N-vinylpyrrolidone, 2.5g of dodecyl methacrylate, 0.12g of N,N'-methylenebisacrylamide, and 4g of sodium acrylamide lignin sulfonate were added sequentially. The mixture was dissolved at 30℃ and 350r / min until it was homogeneous. The pH of the mixture was adjusted to 7.2 with a 10% sodium hydroxide solution. The mixture was stirred at 25℃ and 350r / min for 4h to ensure that the components were fully and evenly dispersed, thus obtaining a physical blend. That is, step S3 did not use low-temperature in-situ copolymerization, but only physical blending. The remaining steps were the same as in Example 15.

[0053] Comparative Example 6: The difference between this filtration loss reducer and Example 15 is that it does not add raw material silane-modified nano-hydroxyapatite, nor does it add N,N'-methylenebisacrylamide (MBA). All other steps are the same as in Example 15.

[0054] Experimental Example 1: To investigate the performance of the core-shell grafted organic-inorganic covalent hybrid filtration loss reducer of the present invention.

[0055] Experimental methods: The performance of the core-shell grafted organic-inorganic covalent hybrid filtration loss reducers prepared in Examples 15 to 19 of this invention was investigated. Comparative Examples 1 to 6 were used as controls. Performance tests included API filtration loss, high temperature and high pressure (HTHP) filtration loss, rheology, shear stability, fluorescence level, and biodegradation rate. The detection methods for each performance are as follows.

[0056] The base slurry preparation includes freshwater-based slurry, saturated brine-based slurry, and high-calcium-based slurry, and the specific preparation methods are as follows: a. Freshwater-based slurry: Measure 400mL of distilled water, add 20g of bentonite for drilling fluid test slurry preparation and 0.7g of anhydrous sodium carbonate, stir at high speed for 20min (interrupted at least twice during which the bentonite on the container wall is scraped off), and cure in a sealed container at room temperature for 24h.

[0057] b. Saturated brine-based slurry: Add analytical grade NaCl to the freshwater-based slurry until saturated (approximately 26% by mass), stir at high speed for 20 minutes, and cure in a sealed environment at room temperature for 24 hours.

[0058] c. High-calcium slurry: Add analytical grade CaCl2 to freshwater slurry to a mass fraction of 10%, stir at high speed for 20 minutes, and cure at room temperature in a sealed environment for 24 hours.

[0059] (1) High temperature thermal aging and API filtration loss test.

[0060] Take 400 mL of each base slurry and add 1.5% by weight of the filtration loss reducing agent sample of each example or comparative example. Stir at high speed for 20 min. Put it into a high-temperature aging tank and place it in a roller heating furnace. Heat and roll at 220℃ for 16 h. For some samples, extend the heat rolling to 32 h. After cooling to room temperature, stir at high speed for 15 min. Measure the API filtration loss according to GB / T 16783.1-2025 standard and record the filtration loss value after 30 min.

[0061] (2) High temperature and high pressure (HTHP) filtration loss test.

[0062] Take 200 mL of the drilling fluid sample after high-temperature aging and measure the HTHP filtration loss using a high-temperature and high-pressure filtration analyzer at 220℃ and 3.5 MPa according to GB / T 16783.1-2025 standard. Record the filtration loss value over 30 minutes. During the test, the back pressure under the 220℃ test condition should not be lower than 3.1 MPa (450 psi) as required by the standard.

[0063] (3) Rheological test.

[0064] Take the above-mentioned aged and cooled drilling fluid sample, and the blank base slurry that has been aged and cooled simultaneously, stir at high speed for 15 min, and let stand for 1 min; according to GB / T 16783.1-2025 standard, use a six-speed rotational viscometer to determine the apparent viscosity (AV), and calculate the viscosity change rate before and after thermal aging according to formula (1). Viscosity change rate before and after thermal aging (%) = (AV1-AV0) / AV0*100, where AV1 is the apparent viscosity of the base slurry after adding the filtration loss reducer, mPa·s, and AV0 is the apparent viscosity of the blank base slurry, mPa·s.

[0065] (4) Shear stability test.

[0066] Take freshwater-based slurry with 1.5% filtration loss reducer and continuously shear it for 1 hour at 12000 r / min using a high-speed mixer; then put it into a high-temperature aging tank and heat-roll it at 220℃ for 16 hours; after cooling, determine the API filtration loss and HTHP filtration loss according to the above method, and calculate the performance retention rate (based on the filtration loss of the unsheared sample).

[0067] (5) Fluorescence level test.

[0068] Standard series preparation: Weigh 0.1g (accurate to 0.01g) of the corresponding oil layer standard oil sample (using crude oil from a certain oilfield) into a test tube, add 10mL of n-hexane, stir well, and determine the fluorescence contrast grade 15. Weigh 5mL of the above-prepared solution, add another 5mL of n-hexane, stir well, and determine the fluorescence contrast grade 14. Repeat the above steps to determine the fluorescence contrast grade from 15 to 1, and seal for later use.

[0069] Fluorescence level test: Add 20 mL of n-hexane to a clean, dried 100 mL beaker, add 1 g (accurate to 0.01 g) of the test sample, shake well, let stand, and allow to clarify. Pour a portion of the clarified liquid into a clean test tube, observe the fluorescence under ultraviolet light, and compare it with relevant standard series to determine the fluorescence level.

[0070] (6) Biodegradation rate test.

[0071] According to GB / T 19277.1-2025 "Determination of final aerobic biodegradation capacity of materials under controlled composting conditions - Part 1: General method", the 28-day aerobic biodegradation rate of the samples was determined. Test conditions: temperature 58℃±2℃, humidity 50%~55%, aeration rate 50mL / min.

[0072] Experimental results: The performance results of the core-shell grafted organic-inorganic covalent hybrid filtration loss reducers prepared in each embodiment of the present invention are shown in Table 1, and the performance results of the filtration loss reducers provided in each comparative example are shown in Table 2.

[0073] Table 1 Performance results of the embodiments .

[0074] Table 2 Performance results of the comparative examples .

[0075] As can be seen from Tables 1 to 2, the core-shell grafted organic-inorganic covalent hybrid filtration reducers prepared in Examples 15 to 19 of this invention are significantly superior to existing mainstream commercial products in terms of high-temperature stability, shear resistance, low viscosity-increasing properties, biodegradability, and salt and calcium resistance. All performance indicators meet the requirements for drilling in ultra-deep, high-temperature, and high-salt formations. The specific advantages of this invention are: First, it exhibits excellent high-temperature stability. Data from Example 15, Comparative Example 1 (commercially available linear NPAM-8000), Comparative Example 3 (commercially available linear AM / AMPS), and Comparative Example 6 (linear copolymer, silane-free modified HAP) in Tables 1 and 2 show that the product prepared in Example 15 exhibits excellent high-temperature stability. After long-term aging at 220°C for 32 hours, its HTHP filtration loss increased from 10.2 mL to 11.6 mL, an increase of only 13.7%; while the HTHP filtration loss of Comparative Example 1 (commercially available linear NPAM-8000) increased from 22.3 mL to 32.7 mL, an increase of 46.6%. The HTHP filtration loss of Example 3 (commercially available linear AM / AMPS) increased from 16.2 mL to 24.6 mL, an increase of 51.9%, demonstrating that the core-shell grafted covalent hybrid structure in the product of this invention can effectively suppress random chain breakage at high temperatures, and its long-term high-temperature stability is significantly better than that of commercially available linear polymer products. Compared with Comparative Example 6 (linear copolymer, without silane-modified HAP), the HTHP filtration loss of Example 15 of this invention (10.2 mL) is significantly lower than that of Comparative Example 6 (17.0 mL), demonstrating that the introduction of a silane-modified nano-hydroxyapatite rigid core in the product of this invention plays a key role in improving temperature resistance. Secondly, the interfacial bonding ability and shear resistance are outstanding. After being subjected to high shear at 12000 r / min for 1 hour, the HTHP filtration loss of the product prepared in Example 15 of this invention increased from 10.2 mL to 10.8 mL, an increase of only 5.9%, with a performance retention rate ≥90%. In contrast, Comparative Example 5 (which did not undergo low-temperature in-situ copolymerization, but only physical blending) showed an increase in HTHP filtration loss from 15.8 mL to 21.7 mL after being subjected to high shear at 12000 r / min for 1 hour, an increase of 37.3%, with significant performance degradation. This demonstrates that the present invention exhibits more stable performance under high-temperature and high-shear conditions, solving the problems of interfacial debonding and agglomeration failure of inorganic particles. Furthermore, it exhibits significant low viscosity increase and good rheological properties. Under the condition of adding 1.5%, the apparent viscosity of the products prepared in Examples 15 to 19 of this invention is only 18 mPa·s to 22 mPa·s, which is at a low level. Based on the apparent viscosity AV0 = 7.5 mPa·s of the blank base slurry, after adding the sample, AV1 = 20 mPa·s (Example 15), with a viscosity increase of 12.5 mPa·s, a small increase. Therefore, the apparent viscosity (18 mPa·s to 22 mPa·s) of the products prepared by this invention is lower than that of similar temperature-resistant filtration loss reducers, proving that this invention can effectively reduce molecular entanglement, achieving improved temperature resistance without increasing viscosity, and exhibiting better rheological properties. Furthermore, the biodegradability is excellent. The products prepared in Examples 15 to 19 of this invention can withstand temperatures up to 220°C, while Comparative Example 4 (commercially available PAC-LV) completely fails at 220°C (API filtration loss increases from 6.8 mL at 180°C to 12.6 mL); the products prepared in each example of this invention have a 28-day biodegradation rate of ≥60%, while the degradation rates of Comparative Example 1 (commercially available linear NPAM-8000) and Comparative Example 3 (commercially available linear AM / AMPS) are both less than 40%, effectively solving the industry problem of "temperature resistance is not environmentally friendly, and environmental protection is not temperature resistant", and is suitable for drilling needs in ecologically sensitive areas; Finally, it exhibits excellent salt and calcium resistance. The product prepared in Example 15 of this invention, after being heated in a saturated brine (NaCl=26%) and 10% CaCl2 system at 220°C for 16 hours, showed an API filtration loss of 4.8 mL to 5.2 mL and an HTHP filtration loss of 11.3 mL to 11.8 mL. The system showed no flocculation, stratification, or precipitation. Therefore, the product of this invention demonstrates significant salt and calcium resistance.

[0076] In summary, the core-shell grafted organic-inorganic covalent hybrid filtration loss reducer of this invention is first obtained by modifying low-cost bio-derived nano-hydroxyapatite with silane. The silane-modified nano-hydroxyapatite then serves as the inorganic core, and organic branches are obtained through surface grafting and copolymerization. It not only exhibits excellent high-temperature stability, outstanding interfacial bonding ability and shear resistance, but also significant low viscosity and good rheological properties. Furthermore, it possesses high biodegradability, good salt and calcium resistance, and low cost. This effectively solves the problems of poor high-temperature stability and poor interfacial bonding and performance failure caused by physical blending of the organic-inorganic interface in existing filtration loss reducers.

[0077] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Unnecessary technical features can be added or removed according to actual needs to meet the needs of different situations.

Claims

1. A core-shell grafted organic-inorganic covalent hybrid filtration loss reducer, characterized in that... The components, by weight, include 3 to 5 parts silane-modified nano-hydroxyapatite, 38 to 42 parts acrylamide, 18 to 22 parts 2-acrylamido-2-methylpropanesulfonic acid, 5 to 7 parts N-vinylpyrrolidone, 2 to 3 parts dodecyl methacrylate, 0.08 to 0.15 parts N,N'-methylenebisacrylamide, 3 to 5 parts sodium acrylamide lignin sulfonate, 0.3 to 0.4 parts composite initiator, and 130 to 140 parts deionized water.

2. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 1, characterized in that... Silane-modified nano-hydroxyapatite is obtained by modifying nano-hydroxyapatite with silane coupling agent KH-570.

3. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 1 or 2, characterized in that... Sodium acrylamide lignin sulfonate is obtained by two-step modification of sodium lignin sulfonate, formaldehyde, dimethylamine and acryloyl chloride.

4. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 3, characterized in that... The composite initiator is composed of ammonium persulfate and sodium bisulfite in a mass ratio of 0.8 to 1.2:0.8 to 1.

2.

5. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 1, 2, or 4, characterized in that... The following steps are required: S1, Preparation of silane-modified nano-hydroxyapatite: Nano-hydroxyapatite was ultrasonically dispersed in water, and then silane coupling agent KH-570 was added to obtain a mixture. After adjusting the pH value of the mixture, the mixture was heated and stirred to react. After centrifugation, washing and drying, silane-modified nano-hydroxyapatite was obtained. S2, Preparation of acrylamide-based sodium lignin sulfonate: Sodium lignin sulfonate was dissolved in sodium hydroxide solution, and the pH was adjusted to 10 to 11. Formaldehyde and dimethylamine were then added and mixed to carry out the Mannich reaction. The system was then cooled, and acryloyl chloride was added to carry out the amidation reaction. After the reaction was completed, the pH was adjusted to 5 to 6, and a precipitate was formed. After washing and drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, Low-temperature in-situ copolymerization: Silane-modified nano-hydroxyapatite is added to deionized water and ultrasonically dispersed. Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, dodecyl methacrylate, N,N'-methylenebisacrylamide and sodium acrylamide lignin sulfonate are added sequentially and stirred until homogeneous to obtain a mixture. The pH value of the mixture is adjusted, and a composite initiator is added to the mixture under a nitrogen atmosphere. After stirring and polymerization reaction, a viscous colloidal polymer is obtained. S4, Post-processing: The viscous colloidal polymer is granulated, dried, crushed and sieved to obtain a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer.

6. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 5, characterized in that... In step S1, the mass ratio of nano-hydroxyapatite to silane coupling agent KH-570 is 1:0.1 to 0.2, and the amount of water added is 9 to 10 times the mass of nano-hydroxyapatite; or / and, in step S1, the pH value of the mixture is adjusted to 8.5 to 9.0 using dilute ammonia water with a mass concentration of 8% to 12%, the temperature is raised to 55℃ to 65℃, and the reaction is stirred for 3.5h to 4.5h; or / and, in step S1, centrifugation is performed at 7500rpm to 8500rpm for 15min to 20min, washing is performed 3 to 4 times with deionized water, and drying is performed under vacuum at 55℃ to 65℃ for 7.5h to 8.5h.

7. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 6, characterized in that... In step S2, the molar ratio of sodium lignosulfonate:formaldehyde:dimethylamine is 1:1.0 to 1.5:1.0 to 1.5, the mass ratio of acryloyl chloride to sodium lignosulfonate is 1:0.4 to 0.8, the mass concentration of sodium hydroxide solution is 8% to 12%, and the amount of sodium hydroxide solution added is 5 to 15 times the mass of sodium lignosulfonate; or / and, in step S2, the Mannich reaction is carried out at 60°C to 70°C for 2 to 3 hours, and the amidation reaction is carried out at 0°C to 5°C for 1 to 2 hours.

8. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 6 or 7, characterized in that... In step S3, during stirring and mixing, the stirring temperature is 25°C to 30°C, the stirring speed is 300 r / min to 350 r / min, and the pH value of the mixture is adjusted to 7.0 to 7.5 using a 10% sodium hydroxide solution; or / and, in step S3, the stirring and polymerization reaction specifically occurs at a stirring rate of 150 r / min to 200 r / min and a temperature of 42°C to 45°C for 3.5 h to 4.0 h.

9. The core-shell grafted organic-inorganic covalent hybrid filtration loss reducer according to claim 8, characterized in that... In step S4, granulation involves feeding the viscous colloidal polymer into an extrusion granulator to produce uniform particles with a particle size of 2 mm to 5 mm, and drying involves drying the particles at 70°C to 75°C for 7.5 h to 8.5 h; or / and, in step S4, sieving involves sieving through an 80-mesh standard sieve.

10. A method for preparing a core-shell grafted organic-inorganic covalent hybrid filtration loss reducing agent according to any one of claims 1 to 4, 6 to 9, characterized in that... Follow these steps: S1, Preparation of silane-modified nano-hydroxyapatite: Nano-hydroxyapatite was ultrasonically dispersed in water, and then silane coupling agent KH-570 was added to obtain a mixture. After adjusting the pH value of the mixture, the mixture was heated and stirred to react. After centrifugation, washing and drying, silane-modified nano-hydroxyapatite was obtained. S2, Preparation of acrylamide-based sodium lignin sulfonate: Sodium lignin sulfonate was dissolved in sodium hydroxide solution, and the pH was adjusted to 10 to 11. Formaldehyde and dimethylamine were then added and mixed to carry out the Mannich reaction. The system was then cooled, and acryloyl chloride was added to carry out the amidation reaction. After the reaction was completed, the pH was adjusted to 5 to 6, and a precipitate was formed. After washing and drying, sodium acrylamide-based sodium lignin sulfonate was obtained. S3, Low-temperature in-situ copolymerization: Silane-modified nano-hydroxyapatite is added to deionized water and ultrasonically dispersed. Acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-vinylpyrrolidone, dodecyl methacrylate, N,N'-methylenebisacrylamide and sodium acrylamide lignin sulfonate are added sequentially and stirred until homogeneous to obtain a mixture. The pH value of the mixture is adjusted, and a composite initiator is added to the mixture under a nitrogen atmosphere. After stirring and polymerization reaction, a viscous colloidal polymer is obtained. S4, Post-processing: The viscous colloidal polymer is granulated, dried, crushed and sieved to obtain a core-shell grafted organic-inorganic covalent hybrid filtration loss reducer.

Citation Information

Patent Citations

  • A method for preparing a hyperbranched polymer for drilling fluid and a drilling fluid

    CN116063623B